# Download Calculus 1c-6, Examples of Taylor's Formula and Limit by Mejlbro L. PDF

April 4, 2017 | | By admin |

By Mejlbro L.

Best software: office software books

Kathy Jacobs On PowerPoint

Learn how to layout displays to slot any viewers, create reviews and graphical essays, use PowerPoint with different Microsoft place of work items, and extra with this timesaving consultant.

Excel 2007 PivotTables Recipes: A Problem-Solution Approach

Debra Dalgleish, Microsoft workplace Excel MVP seeing that 2001, and knowledgeable and coach in Excel, brings jointly a one-stop source for someone fascinated with representing, examining, and utilizing their info with PivotTables and PivotCharts. YouвЂ™ll locate this booklet inimitable whilst dealing with any new or tough challenge in PivotTables, protecting the whole breadth of events you'll ever come upon, from making plans and growing, to formatting and extracting information, to maximizing functionality and troubleshooting.

Microsoft Office Word 2003 Step by Step (Step By Step (Microsoft))

Adventure studying made easy—and quick train your self the best way to use the note processing energy in be aware 2003. With step-by-step, you could take simply the teachings you would like, or paintings from conceal to hide. both means, you force the instruction—building and working towards the abilities you would like, simply if you happen to want them!

Additional resources for Calculus 1c-6, Examples of Taylor's Formula and Limit Processes

Sample text

I. 1) From the series of the exponential we get 2 e−x = 1 − x2 + 1 4 1 6 1 8 x − x + x + x8 ε(x). 2 6 24 Furthermore, cos x = 1 − 1 2 1 4 1 6 1 x + x − x + x8 + x8 ε(x), 2 24 720 40 320 hence f (x) 2 = e−x − cos x 1 1 1 = − x2 + − x4 − 2 2 24 11 4 119 6 1 x − x + = − x2 + 2 24 720 1 1 1 1 − − x6 + 6 6! 24 8! 1679 8 x + x8 ε(x). 40 320 x8 + x8 ε(x) 2) Since 2 f (x) = sin x − 2xe−x = 2 d e−x − cos x , dx one may wrongly conclude that by diﬀerentiation of the result of (1) should obtain 2 f (x) = sin x − 2xe−x 11 3 119 5 1679 7 x − x + = −x + x + x7 ε(x).

I. 1) If f (x) = 2x = ex ln 2 , then f (k) (x) = (ln 2)k · 2x , so (ln 2)k f (k) (0) = , k! k! and the Taylor expansion is n f (x) = 2x = k=0 1 (ln 2)k xk + xn ε(x). k! (x + 2)−k−1 , so f (k) (0) (−1)k = k+1 , k! 2 and the Taylor expansion is f (x) = 1 1 = 2+x 2 n (−1)k k=0 x 2 k + xn ε(x), x into the development which we of course also could have obtained directly by putting y = 2 1 1 . 12 Find the Taylor expansion with the point of expansion x0 = 0 and of any order n for the functions (1) f (x) = sin x + cos x, (2) f (x) = 1 + x2 − 1 − x2 .

And the Taylor expansion is n f (x) = 2x = k=0 1 (ln 2)k xk + xn ε(x). k! (x + 2)−k−1 , so f (k) (0) (−1)k = k+1 , k! 2 and the Taylor expansion is f (x) = 1 1 = 2+x 2 n (−1)k k=0 x 2 k + xn ε(x), x into the development which we of course also could have obtained directly by putting y = 2 1 1 . 12 Find the Taylor expansion with the point of expansion x0 = 0 and of any order n for the functions (1) f (x) = sin x + cos x, (2) f (x) = 1 + x2 − 1 − x2 . A. Taylor expansion for any n. D. Substitute into known developments.